Persepsi Petani Dan Penerapan Teknologi Pengelolaan Tanaman Terpadu Di Desa Sukaresmi Kabupaten Bogor - Elvira Iskandar; Hatipah Nurtilawati (JURNAL AGRIBISNIS TERPADU, 2019)
Integrated crop management (ICM)) is an innovative approach seeking to improve farming productivity and maintains land use sustainability. This study aims to analyze farmers’ perception on ICM technology, factors influencing perception and the influence of farmers' perception on the level of ICM implementation. Data collection was done by using questionnaires and interviews with farmers. Path analysis was used in data analysis by Partial Least Square (PLS) program. The results showed that farmers have a good perception on ICM technology. Factor that significantly influencing perception was farmers' social interaction, reflected by the interaction of farmers and extension agents. The level of perception has a significant and direct effect on the application of ICM technology. The results of path analysis showed that farmers’ characteristics have a direct and significant influence on the technology implementation. Social interaction has an indirect influence through a level of farmers’ perceptions. Farmers' social interaction will awaken farmers' perception, and then the formed perception will influence the attitude of farmers to apply ICM technology.